Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Given the equation in standard form, provide the values of [tex]$a$[/tex], [tex]$b$[/tex], and [tex]$c$[/tex]:

[tex]\[
\frac{2}{3}(x-4)(x+5)=1
\][/tex]

A. [tex]$a = 2; b = 2; c = -43$[/tex]

B. [tex]$a = \frac{2}{3}; b = 1; c = -20$[/tex]

C. [tex]$a = 2; b = 2; c = 43$[/tex]


Sagot :

To convert the given equation

[tex]$ \frac{2}{3}(x-4)(x+5) = 1 $[/tex]

into its standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], we will follow these steps:

1. Expand the left-hand side: Start by expanding the left side of the equation.

[tex]\[ \frac{2}{3}(x-4)(x+5) \][/tex]

Use the distributive property (FOIL method) to expand [tex]\( (x-4)(x+5) \)[/tex]:

[tex]\[ (x-4)(x+5) = x^2 + 5x - 4x - 20 = x^2 + x - 20 \][/tex]

Now multiply this result by [tex]\( \frac{2}{3} \)[/tex]:

[tex]\[ \frac{2}{3} (x^2 + x - 20) = \frac{2}{3}x^2 + \frac{2}{3}x - \frac{40}{3} \][/tex]

2. Subtract 1 from both sides: To move everything to the left-hand side and set the equation to zero, subtract 1 from both sides of the equation:

[tex]\[ \frac{2}{3}x^2 + \frac{2}{3}x - \frac{40}{3} - 1 = 0 \][/tex]

3. Combine constants: [tex]\( - \frac{40}{3} - 1 \)[/tex] can be written as [tex]\( - \frac{40}{3} - \frac{3}{3} = - \frac{43}{3} \)[/tex].

So the equation becomes:

[tex]\[ \frac{2}{3}x^2 + \frac{2}{3}x - \frac{43}{3} = 0 \][/tex]

Now we have the equation in standard form:

[tex]\[ a = \frac{2}{3}, \quad b = \frac{2}{3}, \quad c = - \frac{43}{3} \][/tex]

Given the options:

[tex]\[ (A)\; 2 \quad B = 2 \quad C = -43 \\ (B)\; \frac{2}{3} \quad B = 1 \quad C = -20 \\ (C)\; 2 \quad B = 2 \quad C = 43 \][/tex]

None of the provided options match exactly with the calculated coefficients [tex]\( a, b, \)[/tex] and [tex]\( c \)[/tex]. However, our correct values are:

[tex]\[ a = \frac{2}{3}, \quad b = \frac{2}{3}, \quad c = - \frac{43}{3} \][/tex]

Therefore, if forced to choose from given options, consult the problem constraints and decide accordingly. However, our mathematically correct coefficients do not align with any of the provided options verbatim.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.